German registry for acute aortic dissection type A: structure, results, and future perspectives - Böning, Andreas; Karck, Matthias (The thoracic and cardiovascular surgeon, 2017)
The German Registry for Acute Aortic Dissection Type A (GERAADA) as an international registry for acute aortic dissection type A (AADA) offers a unique opportunity to answer questions regarding acute dissections that cannot be answered by single institution's database alone. GERAADA was started in 2006 by the German Society for Thoracic and Cardiovascular Surgery (GSTCVS) and has collected more than 3,300 AADA patients' data from 56 centers in Germany, Austria, and Switzerland up to now. In the second generated validated dataset comprising the years from 2006 to 2010, 2,137 patients were surgically treated for AADA with an overall 30-day mortality of 16.9%, and a new postoperative neurologic dysfunction of 9.5%. Risk factors for neurologic dysfunction were malperfusion syndromes, dissections of the supra-aortic vessels, and longer operating time. Neuroprotective drugs had no influence on stroke rates. Hypothermic circulatory arrest and antegrade selective cerebral perfusion (ACP) led to similar results if arrest times were less than 30 minutes while ACP for longer arrest periods is advisable. Septuagenarians had an early mortality rate (15.8%) similar to the whole cohort's, but the mortality rate in octogenarians (34.9%) was much higher. GERAADA with its validated 2,137 patient files (2006-2010) is the largest database on AADA worldwide and continues to collect data. Structured follow-up of more than 5 years will be available in the future.